Kajian Antioksidan dan Sifat Sensoris Hasil Pengeringan Daun Ungu (Graptophyllum pictum) dengan Mesin Fast Dryer - Hasanah, Masfufah; Santoso, Agus; Rakhmadevi, Ade Galuh; Fadhila, Putu Tessa (Politeknik Negeri Jember, 2024)
A purple leaf or possibly called a wungu leaf (Graptophyllum pictum) is a commonly used plant as an herbal medicine. Purple leaves have many benefits, and it is known that one can potentially counteract free radicals caused by high flavonoid compounds. One of the key stages in simplishing is the drying method. The study aims to identify the effects of temperature and long periods of drying as well as variations in temperature and length of time on the flavonoid, the sensory properties (color, scent, taste, and texture), water levels, and rendement on the dried purple leaves using fast dryer. The design of the experiments is a Randomized Block Design (RBD). The first factors are drying temperatures consisting of 45°C (C1), 50°C (C2), and 55°C (C3). The second factors is drying time of 3 hours (F1), 4 hours (F2), and 5 hours (F3). The data analysis is done using a ANOVA and if the results show a real difference then a nt test with a 5% confidence level. Studies indicate that the higher the temperature and time spent in drying, the greater the levels of flavonoid and sensory properties and the lower the water content and rendement in dried purple leaf.